Pengendalian Penyakit Tidak Menular Melalui Promosi dan Deteksi Dini - Agustina, Venti; De Fretes, Fiane (Universitas Kristen Satya Wacana Salatiga, 2023)
Management of NCDs is a challenge especially in low- and middle-income countries due to the double burden of communicable and non-communicable diseases, shortage of human and material resources and other competing economic priorities in these countries. This need for promotion and early detection then becomes the background for the implementation of community service, especially for congregations in the JKI Royal Family regarding non-communicable diseases. Community service was carried out for 27 congregations in the JKI Royal Family. This service includes measuring blood pressure, checking blood sugar, uric acid and cholesterol at the same time as providing education which aims to provide an understanding of abnormal examination results along with things that must be avoided. Several findings were obtained, namely 1) the majority of blood pressure examination results blood above 120/80 mmHg, 2) the majority of cholesterol examination results were predominantly more than 200 mmHg, 3) the majority of instant blood sugar and uric acid examination results were normal although values were still found above the normal range. It can be concluded that the community service process went according to schedule and received a positive response from the participants as evidenced by the involvement of the participants from the beginning to the end of the community service process.